Інституціональне забезпечення формування економічної безпеки сільськогосподарських підприємств - Вініченко, Ігор Іванович; Vinichenko, Igor; Ткаліч, Ольга Вікторівна; Tkalich, Olga; Жилін, Ігор Миколайович; Zhylin, Igor (Чорноморський національний університет імені Петра Могили, ТОВ `"ДКС Центр`", 2025)
Встановлено, шо в умовах війни, сільськогосподарське виробництво потребує державної підтримки та урегулювання процесів розвитку агробізнесу з урахуванням умов забезпечення найвищого рівня економічної безпеки. В еволюції теоретичних аспектів розвитку економічної безпеки сільськогосподарських підприємств домінантну роль відіграє інституціональний підхід, який має враховувати децентралізоване географічне положення господарюючих суб'єктів, безпечне використання природних і нематеріальні ресурсів як джерела забезпечення потреб та сприйняття економічної безпеки як незалежності суб'єкта господарювання. Інституційні детермінанти забезпечення економічної безпеки сільськогосподарських підприємств запропоновано трактувати як процес становлення та функціонування системи суспільних інституцій, функціями яких є структурування взаємовідносин між господарюючими суб'єктами, узгодження їх інтересів, формування мотиваційно-поведінкових механізмів інноваційного та соціального характеру, надання гарантій мінімізації впливу загроз в економічному середовищі та сприяння безпеково-стабільному розвитку підприємств відповідно до вимог національних і міжнародних організацій (стандартів).Аргументовано, що ефективний вплив інституцій на забезпечення стійкого стану економічної безпеки сільськогосподарських підприємств дозволяє забезпечити диверсифікацію виробництва та перейти до нових бізнес-моделей, які повинні враховувати ймовірні ризики та загрози. The article establishes that in the conditions of war, agricultural production requires state support and regulation of agribusiness development processes, taking into account the conditions for ensuring the highest level of economic security. In the evolution of theoretical aspects of the development of economic security of agricultural enterprises, the institutional approach takes precedence, which should take into account the decentralized geographical location of economic entities, the secure use of natural and intangible resources asa source of meeting needs, and the perception of economic security as independence of the economic entity. It is substantiated that in the context of instability of the external environment, negative trends in the development of agricultural sectors, overcoming the impact of war, the effective functioning of agricultural enterprises can be achieved only if the principles of a stable state of economic security of economic entities at the institutional level are applied. The institutional determinants of ensuring the economic security of agricultural enterprises are proposed to be interpreted as the process of formation and functioning of a system of public institutions, whose functions are to structure the relations between economic entities, harmonize their interests, form motivational and behavioral mechanisms of innovative and social nature, provide guarantees to minimize the impact of threats in the economic environment and contribute to the security and stable development of enterprises in line with the requirements of national and international organizations (standards). It is determined that the impact of economic security of agricultural enterprises on the development of the country's agrarian economy and individual agricultural sectors is realized through the use of available resources to maximize the reduction of threats and risks and is determined by the nature of economic relations and their constituent elements. The implementation of institutional principles should ensure a stable state of economic security of agricultural enterprises and minimize crisis phenomena (threats) of the external and internal environment, as well as guarantee the stability of their functioning in the following areas: adaptability, continuity, efficiency, expediency, complexity, efficiency and safety. The article provides arguments that the effective influence of institutions on ensuring a sustainable state of economic safety of agricultural enterprises allows for diversification of production and transition to new business models that should consider possible risks and threats.
Institutional support for the formation of economic security of agricultural enterprises
Keywords: бізнес-моделі; Business models; економічна безпека; economic safety; інституції; institutions; інституціональне забезпечення; institutional support; національна безпека; national safety; сталий розвиток; sustainable development; ресурси; resources; ризики; risks; сільське господарство; agriculture